Peran dan Wewenang Pengadilan Tata Usaha Negara Dalam Penyelesaian Sengketa Kepegawaian (Aparatur Sipil Negara) - Syahidin, Rosyad; Sulastri, Dewi (Fakultas Hukum Universitas Islam Batik Surakarta, 2025)
Global developments have impacted the work patterns of State Civil Apparatus (ASN) in Indonesia, thus creating a need for legal protection of ASN rights through labor dispute resolution mechanisms. This study aims to examine the role and authority of the State Administrative Court (PTUN) in resolving labor disputes. Using a normative legal approach and qualitative research methods, this study shows that the PTUN functions as a judicial institution that provides legal protection for special, individual, and final state administrative decisions. However, there are still several practical obstacles, such as overlapping authority with other state administrative institutions, limited understanding of ASN regarding legal procedures, and low compliance with PTUN decisions. To increase the effectiveness of the PTUN in providing justice for ASN, regulatory harmonization, strengthening institutional capacity, and progressive legal interpretation are needed.